Early detection of biochemically occult autonomous thyroid nodules. Issue 6 (December 2016) - Brusca, N; Virili, C; Cellini, M; Capriello, S; Gargano, L; Salvatori, R; Centanni, M; Santaguida, M G
Abstract : Objective: Autonomously functioning thyroid areas may be associated with subclinical or overt hyperthyroidism, but may exist even in the presence of normal TSH. This study was aimed at comparing the rate of autonomously functioning areas and their cardiac sequelae in patients with nodular goitre studied with the usual and a novel approach. Design and methods: In total 490 adult outpatients with thyroid nodular goitre, living in a mild iodine-deficient area, were selected in our referral centre for thyroid diseases from 2009 to 2014 on the basis of a suspicion of thyroid functional autonomy. They were divided in three groups according to a non-conventional approach (excessive response to thyroxine treatment: group 1) or conventional approach (low/normal TSH with clinical suspicion or low TSH: groups 2 and 3). All patients of the study with the suspicion of thyroid functional autonomy underwent thyroid scan with radioactive iodine (I 131 ) uptake (RAIU). Results: The percentage of confirmed thyroid functional autonomy was 319/490, being significantly higher in group 3 than in groups 1 and 2 (81.5 vs 64.7 vs 52.6%; chi-square P  < 0.0001). However, the diagnosis with non-conventional approach was made at a significant earlier age ( P  < 0.0001). Cardiac arrhythmias as well as atrial fibrillation were similarly detected by conventional and non-conventional approaches (chi-square test: P  = 0.2537; P  = 0.8425). Conclusions: The hyper-responsiveness to thyroxine treatment should induce the suspicion of thyroid functional autonomy at an early stage, allowing to detect autonomous functioning areas in apparently euthyroid patients.